Pd-Catalyzed asymmetric allylic amination with isatin using a P,olefin-type chiral ligand with C–N bond axial chirality - Akimoto, Natsume; Takaya, Kaho; Kasashima, Yoshio; Watanabe, Kohei; Yoshida, Yasushi; Mino, Takashi (Beilstein Journal of Organic Chemistry, 2025)
In this study, we implemented the P,olefin-type chiral ligand (aR)-(−)-6, which contains a cyclohexyl group and a cinnamoyl group on the nitrogen atom, in the Pd-catalyzed asymmetric allylic amination of allylic esters with isatin derivatives 11 as nucleophiles. The reaction proceeds efficiently, yielding the products (S)-13 with good-to-high enantioselectivity. A scale-up reaction was also successfully conducted at a 1 mmol scale. Additionally, when malononitrile was added to the resulting product (S)-13a in the presence of FeCl3 as the catalyst, the corresponding malononitrile derivative (S)-16 was obtained without any loss in optical purity.
Keywords: asymmetric allylic amination; axial chirality; isatin; palladium catalysis; P,olefin-type chiral ligand